The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1203/01.pdr.0000227558.14024.57
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Enhances the In Vitro Surface Activity of Dilute Lung Surfactant Preparations and Resists Albumin-Induced Inactivation

Abstract: ABSTRACT:Chitosan is a natural, cationic polysaccharide derived from fully or partially deacetylated chitin. Chitosan is capable of inducing large phospholipid aggregates, closely resembling the function of nonionic polymers tested previously as additives to therapeutic lung surfactants. The effects of chitosan on improving the surface activity of a dilute lung surfactant preparation, bovine lipid extract surfactant (BLES), and on resisting albumin-induced inactivation were studied using a constrained sessile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 39 publications
(64 reference statements)
3
57
0
Order By: Relevance
“…However, we have shown that chitosan effectively decreased the level of LDH leakage more significantly than PEG, independent of pH and concentration. Although the molecular mechanisms of membrane fusion produced by chitosan has yet to be completely understood, Zuo et al suggested that unique hydrophilicity and charge-dependent properties of chitosan induce phospholipid aggregates through the phase transition from a gel to liquid crystalline caused by electrostatic interaction (Zuo et al, 2006). Such membrane integrity assays with a different molecular mass compound emphasized that chitosan was capable of sealing permeabilized membranes by repairing breaches through direct interaction with lipid bilayers.…”
Section: Chitosan Reduces the Disruption Of Cell Membrane Following Tmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have shown that chitosan effectively decreased the level of LDH leakage more significantly than PEG, independent of pH and concentration. Although the molecular mechanisms of membrane fusion produced by chitosan has yet to be completely understood, Zuo et al suggested that unique hydrophilicity and charge-dependent properties of chitosan induce phospholipid aggregates through the phase transition from a gel to liquid crystalline caused by electrostatic interaction (Zuo et al, 2006). Such membrane integrity assays with a different molecular mass compound emphasized that chitosan was capable of sealing permeabilized membranes by repairing breaches through direct interaction with lipid bilayers.…”
Section: Chitosan Reduces the Disruption Of Cell Membrane Following Tmentioning
confidence: 99%
“…Owing to its excellent biocompatibility, biodegradability and low toxicity, chitosan has been extensively investigated as a potential biomaterial in a variety of applications, including drug carriers, wound-healing agents, lung surfactant additives, and tissue engineering scaffolding (Gan and Wang, 2007;Janes et al, 2001;Madihally and Matthew, 1999;Roy et al, 1999;Ueno et al, 1999;Yuan et al, 2004;Zuo et al, 2006). In particular, chitosan is capable of forming large phospholipid aggregates by inducing the fusion of small dipalmitoyl phosphatidylcholine (DPPC) bilayers, which are a major component of the plasma membrane (Pavinatto et al, 2007;Zuo et al, 2006). Thus the use of chitosan as a 'fusogen' might be more advantageous as a potential clinical tool relative to nonionic polymers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such an outcome would be more likely if a specific, nontoxic inhibitor could be identified that would minimize the damaging effects of the albumin-associated PLA 2 . Previous attempts to improve the efficacy of therapies used in the treatment of ARDS patients have focused on the use of various additives, such as chitosan and hyaluronan (HA), which have been shown to be effective in both in vitro and animal models (43,70). One such study has shown that the inhibition of pulmonary surfactant induced by exposure to PLA 2 is attenuated by HA through its ability to diminish the PLA 2 activity (31).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, there is no optimal adjuvant classification. Although the complete working mechanism of many adjuvants is not entirely known at the moment, classification based on their mode of action has been suggested (49,50). Increasing evidence has demonstrated that most non-particulate mucosal adjuvants act by binding to specific receptors, and this adjuvant class is frequently named immunopotentiators.…”
Section: Challenges In Oral and Nasal Vaccine Designmentioning
confidence: 99%